Edukasi Partisipatif Peringatan Dini dan Mitigasi Bencana Hidrometeorologi di Kecamatan Pesanggrahan - Darmawan, Yahya; Karyono, Karyono; Wandono, Wandono; Benyamin Heryanto Rusanto; Agung Perdian Sulistio (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Jakarta, 2025)
Indonesia, as an archipelagic country with a high risk of geo-hydrometeorological disasters, requires early education to build awareness and preparedness. This study aims to improve students’ understanding of early warning systems and disaster mitigation through participatory learning. The Community Service Program (PKM) was carried out at SMA Triguna 1956, Pesanggrahan District, South Jakarta, on July 24, 2025. The stages included site survey, material preparation, socialization through Focus Group Discussion (FGD), disaster response simulation, and evaluation using pre-test and post-test combined with digital media. A quasi-experimental method with a pre-test and post-test design was applied. The results showed a significant increase in students’ understanding of early warning procedures and mitigation measures. Thus, participatory education proved effective in strengthening youth preparedness against geo-hydro meteorological disasters.